Faktor-Faktor Yang Menyumbang Terhadap Kepuasan Kerja Di Kalangan Staf Makmal Sekolah-Sekolah Menengah Awam Di Daerah Kuala Muda/Yan - Lui, Ah Kan (1997)
The aim of this study is to examine the factors that contribute towards the job satisfaction among the lab staff of public secondary schools in the Kuala Muda/Yan District, Apart from the total job satisfaction based on demographic factors such as gender, age, race/origin, marital status, post, and length of service, this study also measures satisfaction levels for all the five dimension of job satisfaction, that is the work itself, pay, promotion, supervision, and co-worker. A total of 75 questionnaires were distributed to the respondents that were made up of the lab staff of public secondary schools in the Kuala Muda/Yan District. Seventy one out of the 75 questionaires returned were found to be usable. The data obtained were analyzed by descriptive and inferential statistics using the computer program of SPSS/PC+ for MS Windows Version. Comparison method, through the t-test and the one-way ANOVA, was used to examine the effects of the demographic factors on job satisfaction. The findings of this study indicate that the total job satisfaction of the lab staff of the public secondary schools in the KMY Districtis is just at the moderate level. Apart from that, it is found that there is a significant difference between the mean total job satisfaction level faced by the lab assisstant and the junior lab assisstant (t = 2.122; p = 0.037). Conversely, the results of this study also indicate that there are no significant differences between the mean total job satisfaction levels faced by the lab staff based on their gender, age, race/origin, marital status, and length of service. From the findings of this study, it is suggested that satisfaction levels with pay and promotion of the lab staff be enhanced through revision of their pay and chances for promotion by the Public Service Department, and the training and development programs designed and implemented at the national, state, district, and school levels be given to the lab staff so that their satisfaction level with the work itself can be enhanced. The lab staff themselves should be more proactive in assisting to enhance their job satisfaction level.